Competencies acquisition through self-directed learning among Malaysian managers - Hashim, Junaidah (Emerald Group Publishing Limited, 2008)
Purpose – The purpose of this paper is to examine how Malaysian managers acquire job competencies through self-directed learning activities at their workplace. Specifically it aims to investigate what types of job competencies are required for the managers, how they learn to acquire those competencies, and whether the managers have the self-directed learning attributes and capability to acquire job competencies by self-directed learning activities. Design/methodology/approach – The data were collected through survey. The survey adapted the Self-Directed Learning Readiness Scale (SDLRS) developed by Guglielmino. In total 238 respondents participated in this study. Findings – The findings show that the respondents have identified communication, managerial, and job knowledge as the main competencies required for their jobs. Most of these competencies are acquired through on-the-job training, working as part of a team and self-education. The findings also reveal that the respondents do possess the attributes of self-directed learners. Research limitations/implications – The findings support previous research. Given the different cultural background of the Malaysian managers, their ways of learning are similar to those of Western managers. Future research can investigate how employees in other professions learn on their jobs and what other factors may influence self-directed learning. Practical implications – Given the emphasis being placed on the importance of work place learning, it is timely to advance a workplace curriculum by integrating the everyday learning experiences and guided learning strategy in the organisation, so that the employees’ learning can be facilitated more effectively. Originality/value – The paper includes the different cultural context of how Malaysian managers learn.